Studies on Preparation and Preservation of Fruit Leather by Blending Bael and Aonla Pulp - Dwivedi, Shailendra K; Mishra, Vigya; Saran, Sunil; Roy, Susanta K (Journal of Postharvest Technology, 2015)
Aonla and bael come under the category of highly nutritious fruits with a high  therapeutic value. Blending of pulp was undertaken in order to prepare a  product rich in vitamins, minerals and antioxidants. Preparation of bael and  aonla blended leather is a low cost technique because being underutilized these  fruits are cheaper in the market. Bael: Aonla fruit leather (2: 1 + 10% sugar)  was prepared with the aonla and bael pulp containing 2000ppm KMS and was  packed in two types of packaging materials viz. aluminium laminated pouches  and polyethylene pouches. The non enzymetic browning maximum recorded in  the products packed in polyethylene pouches at 90 days of storage. Products  packed in aluminium laminated pouches showed a slower increase in NEB as  compared to those packed in polyethylene pouches. A continuous loss was  recorded in the ascorbic acid content from 386.65mg/100g to 350.73mg/100g  in laminated pouches in comparison to 346.16mg/100g in polyethylene  pouches. Total phynolic content decreased from an initial value of 448.41 to  424.34mg/100g in leathers packed in polyethylene pouches against  435.16mg/100g in those packed in laminated. A continuous decrease was  recorded in the colour score of the samples during storage however, a better  colour score was recorded for the leathers packed in laminated pouches as  compared to those packed in polyethylene pouches. Similar findings were  recorded for flavour, texture and overall acceptability of fruit leather. Besides,  the leather is easy to handle and distribute and requires no special storage  conditions. Small entrepreneurs and rural women can easily prepare it at home  and make it available throughout the year.
Keywords: Aonla; Bael; Preservation